Relative reactivity of hydroxyl groups in inositol derivatives: role of metal ion chelation - Devaraj, Subramanian; Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Carbohydrate Research, 2009)
O-Alkylation of myo-inositol derivatives containing more than one hydroxyl group via their alkali metal alkoxides (sodium or lithium) preferentially occurs at a hydroxyl group having a vicinal cis-oxygen atom. In general the observed selectivity is relatively higher for lithium alkoxides than for the corresponding sodium alkoxide. The observed regioselectivity is also dependent on other factors such as the solvent and reaction temperature. A perusal of the results presented in this article as well as those available in the literature suggests that chelation of metal ions by inositol derivatives plays a significant role in the observed regioselectivity. Steric factors associated with the axial or equatorial disposition of the reacting hydroxyl groups do not contribute much to the outcome of these O-alkylation reactions. These results could serve as guidelines in planning synthetic strategies involving other carbohydrates and their derivatives. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbohydrate; Chelation; Cyclitol; Inositol; Protecting group

Orthogonally protected cyclohexanehexols by a ``one reaction - one product'' approach: efficient access to cyclitols and their analogs - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
Differentially protected myo-inositol derivatives were prepared from commercially available myo-inositol through regioselective O-alkylation reactions, which give a single product in each step. These derivatives were converted into six isomeric inositol derivatives carrying orthogonal hydroxy protecting groups. For all these reactions, conditions were chosen to prevent the formation of isomeric products, which obviates the need for separation of isomers and provides the required cyclitol derivative in very good yields. The synthetic potential of these derivatives was illustrated by the conversion of some of the orthogonally protected inositol derivatives into other cyclitol derivatives. Isomeric inositols were also prepared by the global deprotection of all the hydroxy groups.
Keywords: Alkylation; cyclitols; Inositol; Protecting groups; Regioselectivity

Formal synthesis of valiolamine from myo-inositol - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Tetrahedron, 2011)
An efficient formal synthesis of racemic valiolamine starting from readily available myo-inositol is reported. In all the synthetic steps only one regioisomer is formed, which circumvents laborious purification of products. Regioselective benzylation of myo-inositol orthoformate, super-hydride mediated deoxygenation of a cyclitol derivative and stereoselective addition of dichloromethyllithium to an inosose are the key reactions in the synthesis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Amino sugar; Carbohydrate; Cyclitol; Inositol; Natural product; Valiolamine

Orientation of the beta-hydroxyl group controls the diastereoselectivity during the hydride reduction and grignard reaction of inososes - Jagdhane, Rajendra C.; Patil, Madhuri T.; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Tetrahedron, 2013)
A comparison of the results of the Grignard reaction and the hydride reduction of the carbonyl group of epi- and scyllo-inososes reveals that the extent of diastereoselectivity of these reactions is decided by the orientation of the beta-hydroxyl group (or its derivative). Presence of an axial beta-hydroxyl group generally results in the formation of relatively larger amount of the axial alcohol as a result of the reduction of the carbonyl group. The possible reasons for the observed differences in diastereoselectivity between the reactions of these isomeric epi- and scyllo-inososes have been discussed. The sequence of reactions reported here provides convenient access to C-allcylated inositols, such as iso-laminitol and iso-mytilitol as well as 2-O-methyl epi-inositol, an epimer of the naturally occurring ononitol. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; diastereoselectivity; Grignard; Inositol; Nucleophile; reduction